Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Periode 2022-2024 - Syarifah Hatma Ruqayyah Lahibu; Ike Purnamasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the influence of profitability, firm size, and liquidity on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period, the post-COVID-19 pandemic recovery period. Using multiple linear regression with secondary data from financial reports, a purposive sample of 30 companies yielded 89 observations. The results show that liquidity has a significant positive effect on capital structure, while profitability and firm size are partially insignificant. Simultaneously, all three variables are significant, although the low coefficient of determination (7.8%) indicates the influence of other factors. The findings support the Trade-Off and Pecking Order Theories, with implications for financial risk, filling the gap in inconsistent results during the global recovery era.